Working memory maintenance of visual and auditory spatial information relies on supramodal neural codes in the dorsal frontoparietal cortex - Rizza, A; Pedale, T; Mastroberardino, S; Olivetti Belardinelli, M; Van der Lubbe, RHJ; Spence, C; Santangelo, V (MDPI, 2024)
The frontoparietal attention network plays a pivotal role during working memory (WM) maintenance, especially under high-load conditions. Nevertheless, there is ongoing debate regarding whether this network relies on supramodal or modality-specific neural signatures. In this study, we used multi-voxel pattern analysis (MVPA) to evaluate the neural representation of visual versus auditory information during WM maintenance. During fMRI scanning, participants maintained small or large spatial configurations (low- or high-load trials) of either colour shades or sound pitches in WM for later retrieval. Participants were less accurate in retrieving high- vs. low-load trials, demonstrating an effective manipulation of WM load, irrespective of the sensory modality. The frontoparietal regions involved in maintaining high- vs. low-load spatial maps in either sensory modality were highlighted using a conjunction analysis. Widespread activity was found across the dorsal frontoparietal network, peaking on the frontal eye fields and the superior parietal lobule, bilaterally. Within these regions, MVPAs were performed to quantify the pattern of distinctness of visual vs. auditory neural codes during WM maintenance. These analyses failed to reveal distinguishable patterns in the dorsal frontoparietal regions, thus providing support for a common, supramodal neural code associated with the retention of either visual or auditory spatial configurations.